Improving oat yield and lodging resistance through nitrogen fertilization in the Alpine Qinghai-Tibet Plateau - Zhang, Ruifang; Wu, Rui; Liu, Wenhui; Liang, Guoling; Ju, Zeliang (Frontiers in Plant Science, 2026)
BackgroundWith the growing recognition of the nutritional, ecological, and economic importance of oats, global demand for oat production has been steadily increasing. Nitrogen (N) fertilization is a critical agronomic practice for enhancing crop productivity; however, excessive or inappropriate N application often results in lodging during oat growth/. Lodging not only compromises the high-yield potential of oats, but also reduces both grain and forage quality, representing a major constraint to achieving stable and sustainable production.MethodsTo address this issue, two oat cultivars with contrasting lodging resistance—LENA (lodging-resistant) and QY2 (lodging-susceptible)—were evaluated under six N application rates (0, 60, 120, 180, 240, and 300 kg N·ha-¹). Measurements taken at the grain filling stage included agronomic traits, stem mechanical properties, biochemical composition, yield components, and lodging incidence.ResultsIncreasing N application significantly influenced PH, EH, CF2, CF3, and yield-related traits, all of which exhibited a nonlinear response that initially increased and subsequently declined at higher N levels. For LENA, the maximum fresh forage yield (61.78 t·ha-¹), hay yield (19.16 t·ha-¹), and seed yield (6.72 t·ha-¹) were obtained under the N3 treatment (180 kg N·ha-¹). Compared with the N0 control (0 kg N·ha-¹), these yields increased significantly by 19.80%, 21.56%, and 49.13% in 2018 (P < 0.05), and by 33.79%, 31.26%, and 17.12% in 2019 (P < 0.05), respectively. Simultaneously, the basal internode diameter, stem wall thickness of the 2nd and 3rd internodes, stem puncture strength, breaking strength, compressive strength, and lodging-related parameters (lodging rate and lodging index) exhibited an increasing trend with moderate N input. Principal determinants of stem lodging resistance were identified as PH, EH, HCG, basal internode length, and lignin content of the 3rd internode (LI3).ConclusionThis study demonstrates that nitrogen fertilization regulates lodging primarily by affecting the vertical elongation of basal internodes and promoting lignin biosynthesis. Under ecological conditions similar to those of the experimental site, the optimal N application rates for LENA and QY2 were 180 and 60 kg N·ha-¹, respectively. These N regimes effectively balance high yield potential with reduced lodging risk, and can be recommended for adoption in ecologically comparable oat-growing regions.